Enrichment of Omega-3 from Anchovy (Stolephorus sp.) Fish Oil by Enzymatic Hydrolysis - Wawan Kosasih; Raden Tina Rosmalina; Mohamad Robi Muhdani; Dede Zainal Arief; Endang Saepudin; Sri Priatni (Jurnal Kimia Terapan Indonesia, 2020)
Anchovy (Stolephorus sp.) is an economically important fish in Indonesia. Anchovy contains Omega-3 that important to maintain the health of the heart and brain. This study aimed to enrich the Omega 3 content of anchovy oil from the North Sea of West Java. The extraction of anchovy oil was carried out by the soxhlet method. Enrichment of omega 3 from anchovy fish oil is carried out by hydrolysis with a commercial lipase enzyme at concentration 500, 1000, 1500 and 2000 unit/600g fish oil,Â  for 5, 10, 15 and 20 hour. Before hydrolysis, fish oil was added with solvent water, ethanol, toluene, and n-hexane.Â  Omega 3 content of fish oil products were analyzed by using Gas Chromatography (GC) with FID detector with retention time 14.068 min and 15.506 min for Î±-Linolenat (ALA) and eicosapentaenoic (EPA), respectively. The results showed the highest omega 3 content (ALA 0.54% and EPA 1.103% ) was produced by addition n-hexane with a ratio 1:6 with the concentration of lipase was 1000 units for 20 hours.